Asset Pricing Model Uncertainty: A Tradeoff between Bias and Variance. (13th December 2016) - Zhou, Qing
Abstract: This paper draws a parallel between model combination and the mean–variance tradeoff in Modern Portfolio Theory (Markowitz 1952) and proposes a bias–variance tradeoff framework. Building on the bias–variance tradeoff framework, the paper proposes a Model Portfolio Approach (MPA) and a Global Minimum Variance(GMV) weighting scheme to mitigate asset pricing model uncertainty. Using a well‐conditioned pricing covariance estimator, the proposed approach improves out‐of‐sample pricing performance over six widely used asset pricing models, a model selection method and two most popular benchmarks in existing model combination studies, that is, the simple arithmetic average ("1/N") and Ordinary Least Square (OLS) weighting methods.